2019
DOI: 10.1080/0284186x.2019.1585942
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and chemotherapy administration: between empiric and mathematic method review

Abstract: Introduction: Obesity is a major risk factor for chronic disease and cancer development. Therapeutic management of obese patients with cancer is a real challenge for physician because of the alteration of antineoplastic pharmacokinetics parameters in this population. In routine clinical practices, chemotherapy doses in obese patients are arbitrarily capped or adjusted to an ideal weight to minimize excessive toxicities. Material and methods: The main goal of this review is to describe the current state of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Various retrospective studies, pos hoc analyses of clinical trials, and metanalyses have compared survival and chemotherapy toxicity between obese and non-obese patients with cancer, primarily breast and colon cancers, yielding disparate data [14,[42][43][44][45][46]. In a systematic review, Carroll JP et al examined the impact of obesity on adjuvant treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Various retrospective studies, pos hoc analyses of clinical trials, and metanalyses have compared survival and chemotherapy toxicity between obese and non-obese patients with cancer, primarily breast and colon cancers, yielding disparate data [14,[42][43][44][45][46]. In a systematic review, Carroll JP et al examined the impact of obesity on adjuvant treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, capping did not induce more dose reduction in over 2m 2 BSA patients. Bouleftour et al review highlighted the lack of prospective studies focusing on chemotherapy methods of administration in obese patients 22 . Indeed, based on the results of this work, prospective clinical trials are crucial in order to bring scientific proof to this empirical practice.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several retrospective studies in early-stage cancer patients reported that adjuvant chemotherapy dosage was often reduced in obese patients, with a subsequent negative impact on the clinical outcome. 7,9,62,63 Stocker et al, 64 in an exploratory analysis of a PETACC 3 study, showed that dose reduction negatively affected relapse-free survival (RFS) [hazard ratio (HR): 0.48, 95% confidence interval (CI), 0.27-0.85; P ¼ 0.01] with a strong trend toward better OS (HR: 0.53, 95% CI, 0.28-1.01; P ¼ 0.052) in patients with BMI 30 kg/m 2 and BSA 2 m 2 receiving adjuvant chemotherapy for colon cancer. 9 Similarly, the CALGB study 8541 supports the use of full-dose chemotherapy compared with a reduced initial dose due to the improved failure-free survival in obese women (overall adjusted failure risk ratio of 0.73, 95% CI, 0.53-1.00).…”
Section: Evidence-based Chemotherapy Dosing In Overweight and Obese Patientsmentioning
confidence: 99%
“…7,9,62,63 Stocker et al, 64 in an exploratory analysis of a PETACC 3 study, showed that dose reduction negatively affected relapse-free survival (RFS) [hazard ratio (HR): 0.48, 95% confidence interval (CI), 0.27-0.85; P ¼ 0.01] with a strong trend toward better OS (HR: 0.53, 95% CI, 0.28-1.01; P ¼ 0.052) in patients with BMI 30 kg/m 2 and BSA 2 m 2 receiving adjuvant chemotherapy for colon cancer. 9 Similarly, the CALGB study 8541 supports the use of full-dose chemotherapy compared with a reduced initial dose due to the improved failure-free survival in obese women (overall adjusted failure risk ratio of 0.73, 95% CI, 0.53-1.00). 63 The likelihood of receiving a first-cycle dose reduction (<90% of the expected dose) increased in step with the obesity grade, being 11%, 20% and 37% in overweight, obese and severely obese patients, respectively, in a retrospective cohort study of 9672 breast cancer women treated with doxorubicin hydrochloride and cyclophosphamide.…”
Section: Evidence-based Chemotherapy Dosing In Overweight and Obese Patientsmentioning
confidence: 99%
See 1 more Smart Citation